Investigating teacher leadership in Cameroon secondary education : a case of two public schools - Tambe Ebot, Theresia (2018)
Teacher leadership is crucial in improving schools and enhancing student learning. In Cameroon, the hierarchical nature of leadership and the internal school structures encourage the partition of roles and responsibilities and a clear separation of power and authority. Teachers in Cameroon work within a more imposed system, where the national curriculum is design and impose on them. As a result, teachers do not perform activities geared towards leadership. To improve on teacher leadership practices in Cameroon and learn from exemplar systems (e.g., Finland), it is important to examine how teacher leadership is practiced and how it can be improved. Accordingly, the purpose of this study is twofold: investigate teacher leadership practices in Cameroon secondary schools, and explain how teacher leadership practices can be improved. This study used semi-structured interviews, from two public schools in the South West Region of Cameroon. The results suggest that teachers are involved in many different practices, such as teaching, learning, collaborative practices, participation in decision-making, shared professional practices. The results further suggest that teacher leadership can be improved through measures that recognize and motivate the efforts of teachers. Furthermore, when teachers are recognized for their expertise, they become motivated to take their jobs seriously. They can also encourage other staff to work efficiently by devising new strategies to improve on student learning. The findings suggest for future research to examine how teacher leadership practices can improve on student learning.